High Strength Concrete Beams Reinforced with Hooked Steel Fibers under Pure Torsion - Hussain, Haleem K.; Zewair, Mustafa Shareef; Ahmed, Mazin Abdulimam (Salehan Institute of Higher Education, 2022)
A study of the behavior of fibers in high-strength reinforced concrete beams is presented in this paper. Twelve reinforced concrete beams were tested under a pure torsion load. Different compressive strengths (45.2, 64.7, and 84.8 MPa) and fiber volume fractions (0, 0.25, 0.5, and 0.75) with variable spacing between transverse reinforcements have been used. It was discovered that the maximum torque of a high-strength concrete beam is increased by about 20.3, 25.6, and 27.1% when the fractional volume of fiber is increased from 0 to 0.25, 0.5 and 0.75 respectively (when the compressive strength is 45.2 MPa and the transverse reinforcement spacing is 100 mm). The test results show that the ultimate torsional strength becomes higher when the concrete compressive strength increases, and this percentage increase becomes higher with increasing steel fiber volume fraction. When the spacing between transverse reinforcements decreases from 150 to 100 mm, the ultimate torque increases by 19.9%. When the spacing between transverse reinforcements decreases from 100 to 60 mm, the ultimate torque increases by 17.0%. In these beams, the fibersâ€™ compressive strength and volume fraction were kept constant at 45.2 MPa and 0.75, respectively.Â Doi: 10.28991/CEJ-2022-08-01-07 Full Text: PDF